Minimally invasive percutaneous transluminal renal artery stenting. (1st February 2018) - Kongoji, Ken; Mitarai, Takanobu; Kasahara, Mizuho; Yamazaki, Hiroshi; Ishibashi, Yuki; Koyama, Kohei; Yoneyama, Kihei; Tanabe, Yasuhiro; Akashi, Yoshihiro J.; Yoshino, Hideaki
Abstract: Background: Minimally invasive percutaneous transluminal renal artery stenting (MIPTRS) is a method that prevents complications to the greatest extent possible. The present study aimed to investigate the safety and efficacy of MIPTRS performed in cases of renal artery stenosis with an estimated glomerular filtration rate (eGFR) ≤ 45 mL/min. Methods: Cases of patients who underwent MIPTRS at our hospital between December 2010 and June 2015 in whom eGFR was ≤ 45 mL/min were retrospectively analysed. MIPTRS was performed as follows: 1) using a 4Fr sheathless guiding catheter in a trans-radial approach and 2) using a guiding catheter non-touch technique. The amount of contrast agent used was maintained at ≤ 10 mL with 3) carbon dioxide enhancement and 4) intravascular ultrasound guide stenting, and 5) a distal protection device was used. Results: MIPTRS was performed in 22 patients (32 lesions). The pre-MIPTRS creatinine level and eGFR were 2.01 ± 0.88 mg/dL and 29.2 ± 9.0 mL/min/1.73 m 2, respectively. On postoperative day 2, they were 1.78 ± 0.73 mg/dL and 35.1 ± 12.3 mL/min/1.73 m 2 ; at 1 month after the procedure, they were 1.80 ± 0.74 mg/dL and 33.3 ± 12.3 mL/min/1.73 m 2 . Creatinine level did not change significantly, but eGFR was significantly elevated after versus before the procedure, both 2 days later ( p < 0.01) and 1 month later ( p < 0.05). Conclusion: The results of this study demonstrated the usefulness of MIPTRS for protecting renal function. This method can be safely used in patients with decreased renal function.